Analysis of Factors Affecting Islamic Performance of Nurses in Central Surgery Installation of Sultan Agung Islamic Hospital - Maharani, Virgi Mayang; Jati, Sutopo Patria; Nugraheni, Sri Achadi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Islamic performance of nurses in the Central Surgical Installation (CSI) Sultan Agung Islamic Hospital (SAIH) is one of the important aspects in assessing performance as a sharia hospital. This study aims to determine the relationship between leadership, job design, supervision, motivation, personal values of religiosity, personal values of spirituality and job satisfaction on the Islamic performance of CSI SAIH nurses. The research method used is observational with a cross-sectional design. The sample used is a nurse implementing CSI SAIH with saturated sampling. The research was analyzed by a bivariate test with chi-square and multivariate logistic regression test. The results of this study showed that there was a significant relationship between leadership (OR 4.898 p=0.026), job design (OR 2.494 p=0.231) supervision (OR 18.909 p=0.002), motivation (OR 2.571 p = 0.234), personal religiosity (OR 4.333 p = 0.041), personal spirituality value (OR 5.455 p = 0.023), job satisfaction (OR 7.292 p = 0.022) on the Islamic performance of nurses. Multivariate analysis obtained supervision variable (OR 26,351 p=0,009) and personal spiritual value (OR 7,519 p=0,019). The variables of leadership, supervision, personal values of religiosity, personal values of spirituality and job satisfaction have an effect on Islamic performance. The supervision variable is the most influential variable on Islamic performance.Abstrak: Kinerja islami perawat Instalasi Bedah Sentral (IBS) Rumah Sakit Islam Sultan Agung (RSISA) merupakan salah satu aspek penting dalam penilaian kinerja sebagai rumah sakit syariah. Penelitian ini bertujuan untuk mengetahui hubungan antara kepemimpinan, desain pekerjaan, supervisi, motivasi, nilai pribadi religusitas, nilai pribadi spiritualitas dan kepuasan kerja terhadap kinerja islami perawat IBS RSISA. Metode penelitian yang digunakan adalah observasional dengan desain cross sectional. Sampel yang digunakan adalah perawat pelaksana IBS RSISA dengan pengambilan sampel jenuh. Instrumen penelitian yang digunakan adalah dengan kuesioner yang akan diolah dan dianalisis dengan uji bivariat dengan chi square dan multivariat dengan uji regresi logistik. Hasil penelitian ini didapatkan ada hubungan yang bermakna antara kepemimpinan (OR 4,898, p=0,026), desain pekerjaan (OR 2,494, p=0,231) supervisi (OR 18,909, p=0,002), motivasi (OR 2,571, p = 0,234), nilai pribadi religiusitas (OR 4,333, p=0,041), nilai pribadi spiritualitas (OR 5,455, p=0,023), kepuasan kerja (OR 7,292, p=0,022) terhadap kinerja islami perawat. Analisis multivariat didapatkan variabel supervisi (OR 26,351, p=0,009) dan nilai pribadi spiritual (OR 7,519, p=0,019). Variabel kepemimpinan, supervisi, nilai pribadi religiusitas, nilai pribadi spiritualitas serta kepuasan kerja berpengaruh terhadap kinerja islami. Variabel supervisi merupakan variabel yang paling berpengaruh terhadap kinerja islami.